Making Sense Of Life In 2017 - Metaphors Of The Internet - Markham, Annette; Lingel, Jessa; Møller, Kristian; Driscoll, Kevin; Warfield, Katie (AoIR Selected Papers of Internet Research, 2017)
Various metaphors are used to make sense of and explain our experiences with and in digital, web, internet-mediated, or technologically saturated contexts. These thrive and dwindle as our rhetoric moves from Cyberspace and the Electronic Frontier to the World Wide Web, social network sites and networked publics. The more ubiquitous networked communication becomes, the more it is articulated as a way of being, and the more banal and invisible its properties become. Studying metaphors offers important insights about how people and groups make sense of their experience, construct the world and attribute value to various phenomena. Yet, whatever metaphor is chosen, it concurrently illuminates and distorts what we see of the world and how we understand it. This panel brings together five presentations that engage with the three-pronged metaphorical framework of the internet as a tool, a place and a way of being suggested by Annette Markham in 1998. Today, 20 years later, authors examine various commonly invoked metaphors about the internet, networked technology or socially mediated experiences and utilize or extend the original framework. Combined, the papers explore the metaphors used by people and in large discourse; how dominant metaphors shift in time, and the political, ideological and methodological implications of these metaphors.